C11orf95‐RELA fusion present in a primary intracranial extra‐axial ependymoma: Report of a case with literature review. Issue 5 (28th April 2016) - Nambirajan, Aruna; Malgulwar, Prit Benny; Sharma, Mehar C.; Singh, Anutosh; Pathak, Pankaj; Satyarthee, Guru Dutta; Garg, Ajay
Abstract : Ependymomas are gliomas that recapitulate the ependymal cells microscopically and ultrastructurally. They commonly occur along the ventricular surfaces and central canal of the brain and spinal cord. Intracranial extra‐axial ependymoma (IEAE) is a rare entity and is commonly misdiagnosed clinically and radiologically as a meningioma. The histogenesis of such IEAEs is obscure. A novel recurrent oncogenic fusion involving the C11orf95 and RELA genes was recently described in supratentorial ependymomas. A 9‐year‐old girl presented with a dural based parafalcine mass that, in addition to exhibiting classical immunohistochemical features of an ependymoma, also demonstrated C11orf95‐RELA fusion, characteristic of supratentorial ependymomas. We suggest that IEAEs share their histogenesis with their intra‐axial counterparts, arising either from dural extension of subcortical, subependymal rests or directly from ectopic dural rests.